Rehabilitation of Patients with Paraplegia from Spinal Cord Injury: A Review (Journal of Chittagong Medical College Teachers' Association, 2010)
DOI: 10.3329/jcmcta.v20i1.4937 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):53-57